The Implementation Of Lesson Study Method In Teaching Procedure Text By Utilizing Real Object Recycled In The Tenth Grade Of Ma Ummul Quro At-Tarbawiyah Pamekasan - Rofiqi, Ach Aldi; Rohaniyah, Jaftiyatur (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This research is motivated by the fact that students' learning activities in english lesson are less enthusiastic and more silent, resulting in a lack of active atmosphere in the learning process. This research aims to determine the implementation of lesson study in learning text procedures using recycled media data in class X MA Ummul Quro At-Tarbawiyah, which consists of 15 students. Apart from that, the lesson study method is applied at this school by 3 English teachers and researcher. 1 person as a model teacher, and 3 people as observers. The researcher used descriptive qualitative method in this research. The data obtained is in the form of documentation such as photos and the results of researchers' observations at each step of the lesson study process. The research results showed that the implementation of lesson study to identify students' learning activeness was carried out in two cycles with the stages plan, do, see. The indicators of activeness identified are the teacher's ability to apply each stage of lesson study, and the student's ability to study the material provided. This research has been said to be going well, marked by the achievement of the indicators needed by researchers. With lesson study, you can identify students' activeness in learning. Based on the results of this research, it is recommended that this research only discuss how to implement lesson study in the process of learning text procedures using recycled media and what are thew benefits of lesson study method. Therefore, similar research regarding the implementation of lesson study can examine other learning processes.